Fusion primer driven racket PCR: A novel tool for genome walking - Pei, Jinfeng; Sun, Tianyi; Wang, Lingqin; Pan, Zhenkang; Guo, Xinyue; Li, Haixing (Frontiers in Genetics, 2022)
The available genome-walking strategies have suffered from low level of specificity, strong background, or cumbersome experimental process. Herein, we report a genome-walking method, called fusion primer driven racket PCR (FPR-PCR), for reliable retrieving unknown flanking DNA sequences. Four sequence-specific primers (SSP1, SSP2, SSP3, and SSP4) were sequentially selected from known DNA (5'→3') to complete FPR-PCR. SSP3 is the fragment mediating intra-strand annealing (FISA). The FISA fragment is attached to 5’ end of the SSP1, generating a fusion primer. The FPR-PCR comprises two rounds of amplification reactions. The single fusion primer-driven primary FPR-PCR begins with the selective synthesis of target first-strand; then allows the primer to partially anneal to some place(s) on unknown region of this strand, producing the target second-strand. Afterwards, a new first-strand is synthesized using the second-strand as template. This new first-strand 3’ end undergoes intra-strand annealing to the FISA site, followed by forming a racket-like DNA by a loop-back extension. This racket-like DNA is exponentially amplified in the secondary FPR-PCR performed by SSP2 and SSP4. The FPR-PCR was validated by identifying the unknown flanks of Lactobacillus brevis CD0817 glutamic acid decarboxylase genes and rice hygromycin gene. Compared to the existing genome-walking methods, FPR-PCR has at least one superiority of specificity, probability of success, or efficiency.